Organic Memristor Utilizing Copper Phthalocyanine Nanowires with Infrared Response and Cation Regulating Properties. (3rd January 2019) - Lv, Ziyu; Hu, Qikun; Xu, Zong‐Xiang; Wang, Junjie; Chen, Zhonghui; Wang, Yan; Chen, Meng; Zhou, Kui; Zhou, Ye; Han, Su‐Ting
Abstract: Current organic memristive devices have been suffering from unstable performance, ambiguous mechanism, and poor NIR response, thus restricting their commercial translation. Here, a near‐infrared‐sensitive (NIR) organic memristive device with high stability based on solution‐processed copper phthalocyanine nanowires (N‐CuMe2 Pc NWs) is first reported. Compared with uneven thermal evaporated N‐CuMe2 Pc film, the N‐CuMe2 Pc NWs film possesses a uniform 3D mesh structure, which attribute to the localized cationic migration, robust formation/rupture of conductive filament and subsequent improvement of reproducibility, thermal stability, and retention characteristics. Furthermore, operating voltage and OFF current can be readily regulated by NIR illumination due to strong NIR absorption of the well‐aligned edge‐to‐edge interconnected N‐CuMe2 Pc NWs and tunable potential barrier formed between active layer and Ag electrode, which are further verified by absorption spectrum and Kelvin probe force microscope analysis, respectively. This study provides a generalized method for optimizing device performance and attaching phototunable properties of organic memristive memories. In addition, compared with pristine CuPc molecules with low solubility, limitation of thermal evaporation approach that is incompatible with scaling up is expected to overcome by the solution‐processed N‐CuMe2 Pc NWs. Abstract : The organic memristor based on solution‐proceesed N‐CuMe2 Pc nanowires is demonstrated . The device exhibits high reproducibility, thermal stability, endurance due to well‐manipulated Ag + cation injection path in mesh‐structural nanowire film through nanoconfinement of the molecules into well‐aligned edge‐to‐edge interconnected nanowires. Furthermore, the solution‐processed N‐CuMe2 Pc NWs exhibit strong extinction at wavelength of 788 nm, which ensures the NIR light‐controlled resistive switching.